Plastic-dipped flame-retardant elevator balance compensation chain and preparation method thereof
By using modified high-strength alloys and modified environmentally friendly flame-retardant PVC powder in the elevator compensation chain, combined with plasma surface modification technology and dip plastic treatment, the problem of insufficient flame retardant performance of the existing elevator compensation chain in the fire situation is solved. , achieves higher flame retardant performance and service life, and ensures environmental protection and high efficiency during the preparation process.
Patent Information
- Application Number
- CN202411603308.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing elevator compensation chain is difficult to effectively delay the spread of the fire in the event of fire, and it is difficult to ensure the efficiency of environmental protection and flame retardant performance during the preparation process.
The modified high-strength alloy and modified environmentally friendly flame-retardant PVC powder are used to treat the alloy surface through plasma surface modification technology, and the modified environmentally friendly flame-retardant PVC powder is immersed in plastic treatment to form a protective layer to improve flame-retardant performance.
It significantly improves the flame retardant performance and service life of the elevator balance compensation chain, effectively delays the spread of fire in the case of fire, and ensures environmental protection and high efficiency during the preparation process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of elevator compensation chain preparation, and in particular to a plastic-dipped flame-retardant elevator balance compensation chain and a preparation method thereof. Background Art
[0002] The elevator compensation chain ensures the stability of the elevator during operation by balancing the weight difference caused by the change in the length of the traction wire rope on both sides of the car and the counterweight. The existing elevator compensation chain is difficult to effectively delay the spread of fire when encountering emergencies such as fire, and may even cause more serious safety accidents.
[0003] The defects of the existing elevator balance compensation chain preparation are: 1. Patent document CN104140600B discloses a halogen-free and environmentally friendly high-speed elevator compensation chain material and its application. It mainly considers how to achieve the halogen-free environmental protection requirements of the entire elevator system, but does not consider how to improve the flame retardant performance of the compensation chain, thereby delaying the spread of fire in the event of a fire; 2. Patent document CN103865200B discloses a method for preparing an environmentally friendly high-speed elevator compensation chain sheath material. The method mainly considers how to make the compensation chain sheath have excellent strength and elongation to ensure that the cable will not break during operation, but does not consider how to optimize the surface treatment to significantly increase the service life of the compensation chain without using harmful substances. 3. Patent document CN106245390B discloses a process for preparing aging-resistant elevator compensation cables. It mainly considers how to improve the corrosion resistance and aging resistance of the compensation cables, but does not consider multi-step screening during the preparation process, making it difficult to ensure the quality and performance of the prepared compensation chain. 4. It is difficult to efficiently prepare environmentally friendly flame retardants with high flame retardancy during the preparation process of existing compensation chains, and it is difficult to ensure the flame retardancy of the compensation chains. Summary of the invention
[0004] The object of the present invention is to provide a plastic-impregnated flame-retardant elevator balance compensation chain and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a plastic dip flame retardant elevator balance compensation chain, characterized in that it comprises the following raw materials: modified high-strength alloy and modified environmentally friendly flame retardant PVC powder; The modified high-strength alloy is prepared by subjecting the high-strength alloy to plasma surface modification treatment; The modified environmentally friendly flame-retardant PVC powder is prepared from PVC resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant in a mass ratio of 2:1:(0.1-1):0.3:0.2:0.1:0.3:0.2; The modified high-strength alloy is assembled into a compensation chain, and then the preheated compensation chain is completely immersed in modified environmentally friendly flame-retardant PVC powder to obtain a flame-retardant compensation chain, which has better flame-retardant properties than the existing plastic-coated compensation chain.
[0006] Preferably, the halogen-free composite flame retardant is prepared by mixing modified basic magnesium sulfate whiskers and bisphenol A-bis(diphenyl phosphate) in a mass ratio of 2:(1-4).
[0007] Preferably, the particle size of the modified environmentally friendly flame-retardant PVC powder is 1-3 mm.
[0008] Preferably, the preparation method of the plastic-impregnated flame-retardant elevator balance compensation chain is as follows: Step S1: material pretreatment: performing plasma surface modification treatment on the high-strength alloy to obtain a modified high-strength alloy, and selecting the modified high-strength alloy of qualified quality as the preparation raw material; Step S2: Chain production and assembly: Cut and shape the qualified modified high-strength alloy selected in step S1 to make standard chain links, and then connect and weld the chain links one by one to form a complete compensation chain; Step S3: preparing modified environmentally friendly flame-retardant PVC powder: mixing PVC resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant in a mass ratio of 2:1:(0.1-1):0.3:0.2:0.1:0.3:0.2 to prepare environmentally friendly flame-retardant PVC, then grinding the environmentally friendly flame-retardant PVC into powder, and fluidizing the powder for standby use; Step S4: plastic dipping: the compensation chain obtained in step S2 is subjected to plastic dipping treatment to form a protective layer on the surface of the compensation chain; Step S5: Performance test: The compensating chain obtained in step S4 is subjected to mechanical property test, corrosion resistance test and flame retardant property test.
[0009] Preferably, the step S1 further includes the following steps: Step S11: Materials and cleaning: First, clean the high-strength alloy with clean water to remove dust and oil on the surface; Step S12: Surface cleaning: The high-strength alloy cleaned in step S11 is then placed in a low-temperature vacuum plasma surface treatment apparatus, and the oxides and other stubborn contaminants on the surface of the high-strength alloy are removed by plasma cleaning technology in a vacuum environment; Step S13: Surface etching: Physically etching the high-strength alloy cleaned in step S12 to make the surface of the high-strength alloy rough; Step S14: Surface activation: Then, the high-strength alloy etched in step S13 is plasma activated to change the chemical activity of the surface of the high-strength alloy; Step S15: plasma polymerization: methane gas is then introduced into the low-temperature vacuum plasma surface treatment apparatus to perform a polymerization reaction in a plasma state to form a 1-2 mm polymer coating on the surface of the high-strength alloy; Step S16: Subsequent treatment: Finally, heat treatment is performed on the high-strength alloy polymerized in step S15; Step S17: Quality screening: Perform adhesion test and corrosion resistance test on the modified high-strength alloy according to the provisions of GB / T38020.2-2019, and remove unqualified modified high-strength alloy.
[0010] Preferably, the step S2 further includes the following steps: Step S21: cutting: using a laser cutting machine to cut the modified high-strength alloy; Step S22: Cleaning: Then use an ultrasonic cleaning machine to clean the cut alloy to remove debris and impurities on the surface; Step S23: forming: using a chain forming machine to bend and press the alloy cleaned in step S22 to form chain links; Step S24: Assembling: connecting the formed chain links one by one to form a continuous chain by an automated welding robot; Step S25: Screening: Use visual inspection equipment to detect whether the size of the chain formed in step S24 meets the predetermined size standard, and screen out chains with unqualified sizes.
[0011] Preferably, the step S3 further includes the following steps: Step S31: mixing the basic magnesium sulfate whisker with deionized water, stirring at a speed of 30-50 rpm for 10-20 minutes, and heating to 70°C, then adding a surface modifier thereto and continuing stirring for 15 minutes to obtain a modified basic magnesium sulfate whisker solution, wherein the mass ratio of the basic magnesium sulfate whisker to the surface modifier is 10:1, cooling the solution to room temperature, washing with clean water, and then drying at room temperature to obtain modified basic magnesium sulfate whiskers; Step S32: mixing the modified basic magnesium sulfate whisker obtained in step S31 with bisphenol A-bis(diphenyl phosphate) in a mass ratio of 2:(1-4) at 40-50° C. to obtain a halogen-free composite flame retardant; Step S33: placing PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant and antioxidant in a high-speed mixer, stirring at 650-800 rpm for 15 min at 85-90° C., then cooling to room temperature, then adding halogen-free composite flame retardant and smoke suppressant to the high-speed mixer, and continuing to stir at 650-800 rpm for 5 min at room temperature to obtain a premix; Step S34: adding the premixed material in step S33 into a twin-screw extruder, extruding strips through the extruder, and then cooling the extruded strips and cutting them into PVC particles, wherein the temperature of the extruder is 165-170° C.; Step S35: Rapidly cool the PVC particles in step S34 by passing through a cooling water bath, and then dry them at room temperature to remove moisture from the surface of the particles; Step S36: The PVC particles are then crushed by a high-speed rotating grinder, and then screened by a filter to obtain modified environmentally friendly flame-retardant PVC powder; Step S37: Then add the fumed silica to the modified environmentally friendly flame-retardant PVC powder, stir evenly to obtain a mixed powder, and then place the mixed powder in a fluidized bed, supply nitrogen to the fluidized bed at an air flow rate of 40 to 60 cm / s, so that the modified environmentally friendly flame-retardant PVC powder forms a suspended state in the fluidized bed, and obtain the modified environmentally friendly flame-retardant PVC powder in a fluidized state for use.
[0012] Preferably, the step S4 further includes the following steps: Step S41: firstly install the compensation chain on the hanger, and then preheat the compensation chain on the hanger, wherein the heating temperature of the preheating treatment is 180° C. to 200° C., and the heating time is 10 minutes; Step S42: then immerse the preheated compensation chain in a fluidized bed filled with modified environmentally friendly flame-retardant PVC powder in a fluidized state for 5-10 minutes, and then send the dipped compensation chain into an oven for heating and curing at a temperature of 190°C to 200°C for 2 minutes; Step S43: Then, the baked compensation chain is subjected to air cooling treatment to fix the coating on the surface of the compensation chain, and then the cooled compensation chain is removed from the hanger.
[0013] Preferably, the step S5 further includes the following steps: Step S51: inspect the mechanical properties of the compensation chain according to the inspection method specified in GB / T2951.11-2008, and then conduct a neutral salt spray test for 360 hours according to the method specified in GB / T10125-2012, and then measure the actual breaking load according to the method specified in T / CEA0027-2021 to determine the corrosion resistance of the compensation chain; Step S52: Flame retardant performance test: fix the compensation chain sample vertically on the sample fixture in the combustion tube, use the igniter to ignite the top of the sample, introduce a mixed gas of oxygen and nitrogen into it, and adjust the flow ratio of oxygen and nitrogen to measure the minimum oxygen concentration that can just maintain combustion to evaluate the flame retardant performance of the compensation chain.
[0014] Preferably, the temperature of the fluidized bed in step S37 is maintained at 60°C-70°C.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention mixes PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant, antioxidant, halogen-free compound flame retardant and smoke suppressant in a certain order and proportion to prepare a pollution-free modified PVC with excellent flame retardancy and mechanical properties. The modified environmentally friendly flame retardant PVC is dip-molded on the outside of the chain to form a dip-molded protective layer, which not only provides a protective effect and prolongs the service life of the compensation chain to improve the performance retention rate of the compensation chain in long-term use, but also effectively delays the spread of fire in emergency situations such as fire due to the excellent flame retardancy of the dip-molded layer.
[0016] 2. The present invention uses plasma surface modification technology to perform surface treatment on high-strength alloys. Without using harmful substances, the corrosion resistance and wear resistance of high-strength alloys can be improved, and the service life of the compensation chain prepared later can be significantly improved. First, pollutants such as grease and oxides on the alloy surface are completely removed, and then the surface of the compensation chain material is physically etched by ions and neutral substances in the plasma to make its surface rough and increase the surface area, thereby improving the adhesion of subsequent coatings. Then, plasma activation is used to break the covalent bonds on the surface of the original material, and new functional groups such as carboxyl (-COOH) and hydroxyl (-OH) are introduced to change the chemical activity of the material surface. Then, a thin polymer coating is formed on the surface of the compensation chain material by controlling the polymerization reaction of the organic compound gas methane in the plasma state. On the formed polymer coating, branched chains are introduced by grafting to form a new surface layer to improve the wear resistance of the alloy. Then, heat treatment is performed to further stabilize the surface properties of the alloy.
[0017] 3. The present invention improves the mechanical properties and corrosion resistance of the finally prepared compensation chain through multi-step screening during the preparation process. After surface treatment of the high-strength alloy, the modified high-strength alloy with unqualified performance is screened out through testing. After cutting and assembling these modified high-strength alloys into chains, the assembled chains are tested for size by visual inspection equipment to check whether the size of the chain meets the preset size, and the chains with unqualified size are removed. By improving the quality of the main body of the prepared compensation chain, the overall quality and performance of the subsequently prepared compensation chain are further improved, and the success rate of the preparation of the compensation chain is improved. At the same time, the use of automated welding robots during assembly can reduce human errors, improve the assembly welding quality, and thereby improve production efficiency and product quality.
[0018] 4. The present invention uses a surface modifier to modify the basic magnesium sulfate whisker, so that the modified basic magnesium sulfate whisker reduces the adverse reaction with the polymer matrix. After the surface modification, the subsequent compatibility and dispersibility of the basic magnesium sulfate whisker with the resin matrix can be significantly improved, and the mechanical strength and flame retardant properties of the PVC material are further improved. The modified basic magnesium sulfate whisker is mixed with bisphenol A-bis(diphenyl phosphate) in proportion to prepare a halogen-free composite flame retardant. The flame retardant has good thermal stability and low toxicity, and can act through the condensed phase and the gas phase at the same time, effectively delaying the burning speed of the material and reducing the smoke release during combustion, so as to improve the flame retardant properties of the subsequently prepared modified environmentally friendly flame-retardant PVC, thereby effectively improving the flame retardant properties of the compensation chain. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention provides a plastic dip flame retardant elevator balance compensation chain and a preparation method thereof. The preparation method of the plastic dip flame retardant elevator balance compensation chain is as follows: Step S1: material pretreatment: first, simply clean the high-strength alloy with clean water to remove dust and oil on the surface, then place the cleaned high-strength alloy in a low-temperature vacuum plasma surface treatment instrument, and use plasma cleaning technology in a vacuum environment to remove oxides and other stubborn pollutants on the surface of the high-strength alloy, then physically etch the cleaned high-strength alloy to make the surface of the high-strength alloy rough, then plasma activate the etched high-strength alloy to change the chemical activity of the surface of the high-strength alloy, then introduce methane gas into the low-temperature vacuum plasma surface treatment instrument, perform polymerization reaction in a plasma state, and form a 1-2mm polymer coating on the surface of the high-strength alloy, finally heat treat the polymerized high-strength alloy, then perform adhesion test and corrosion resistance test on the modified high-strength alloy according to the contents specified in GB / T38020.2-2019, and remove unqualified modified high-strength alloy; Step S2: Chain production and assembly: Use a laser cutting machine to cut the qualified modified high-strength alloy selected in step S1, then use an ultrasonic cleaning machine to clean the cut alloy to remove surface debris and impurities, then use a chain forming machine to bend and press the alloy to form chain links, and then use an automated welding robot to connect the formed chain links one by one to form a continuous chain, and finally use a visual inspection device to detect whether the size of the chain formed in step S24 meets the predetermined size standard, and screen out chains with unqualified sizes; Step S3: preparing modified environmentally friendly flame-retardant PVC powder: firstly, mixing basic magnesium sulfate whiskers with deionized water, stirring at a speed of 30-50 rpm for 10-20 minutes, and heating to 70°C, then adding a surface modifier thereto and continuing stirring for 15 minutes to obtain a modified basic magnesium sulfate whisker solution, wherein the mass ratio of basic magnesium sulfate whiskers to surface modifier is 10:1 solution, cooling the solution to room temperature, washing with clean water, and then drying at room temperature to obtain modified basic magnesium sulfate whiskers. The modified basic magnesium sulfate whisker is then mixed with bisphenol A-bis(diphenyl phosphate) at a mass ratio of 2:(1-4) at 40-50°C to obtain a halogen-free composite flame retardant. PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant and antioxidant are then placed in a high-speed mixer, stirred at 650-800 rpm for 15 minutes at 85-90°C, and then cooled to room temperature. The halogen-free composite flame retardant is then added to the high-speed mixer. agent and smoke suppressant, and continue to stir at a speed of 650-800rpm for 5min at room temperature to obtain a premix, then add the mixed premix into a twin-screw extruder, extrude strips through the extruder, and then cool the extruded strips and cut them into PVC particles, wherein the temperature of the extruder is 165-170°C, then quickly cool the PVC particles through a cooling water bath, then dry them at room temperature to remove moisture on the surface of the particles, then crush the PVC particles through a high-speed rotating grinder, and then use a filter to screen them to obtain modified environmentally friendly flame-retardant PVC powder, then add fumed silica to the modified environmentally friendly flame-retardant PVC powder, stir evenly to obtain a mixed powder, then place the mixed powder in a fluidized bed, supply nitrogen to the fluidized bed at an air flow rate of 40-60cm / s, so that the modified environmentally friendly flame-retardant PVC powder forms a suspended state in the fluidized bed, and obtain a fluidized modified environmentally friendly flame-retardant PVC powder for standby use, wherein the temperature of the fluidized bed is maintained at 60°C-70°C; Step S4: Dipping: first install the compensation chain on the hanger, and then preheat the compensation chain on the hanger, wherein the heating temperature of the preheating treatment is 180℃~200℃, and the heating time is 10min, then immerse the preheated compensation chain in a fluidized bed filled with fluidized modified environmentally friendly flame-retardant PVC powder, and keep it for 5-10min, then send the dipped compensation chain into the oven for heating and curing, the heating temperature is 190℃~200℃, and the duration is 2min, then the baked compensation chain is air-cooled to fix the coating on the surface of the compensation chain, and then the cooled compensation chain is removed from the hanger.
[0021] Further, the value in step S3 is changed, and steps S1-2 and S4 are performed, and then the prepared compensation chain is subjected to mechanical property tests, corrosion resistance tests, and flame retardancy tests.
[0022] Embodiment 1: Step S3: preparing modified environmentally friendly flame-retardant PVC powder: firstly, mixing basic magnesium sulfate whiskers with deionized water, stirring at 40 rpm for 20 min, and heating to 70°C, then adding a surface modifier thereto and continuing stirring for 15 min to obtain a modified basic magnesium sulfate whisker solution, wherein the mass ratio of basic magnesium sulfate whiskers to surface modifier is 10:1 solution, cooling the solution to room temperature and then washing with clean water, and then drying at room temperature to obtain modified basic magnesium sulfate whiskers, and then drying the obtained modified basic magnesium sulfate whiskers The mixture was mixed with bisphenol A-bis(diphenyl phosphate) at a mass ratio of 2:1 at 50°C to obtain a halogen-free compound flame retardant. Then, PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant and antioxidant were placed in a high-speed mixer and stirred at 700 rpm for 15 minutes at 85°C, then cooled to room temperature, and then the halogen-free compound flame retardant and smoke suppressant were added to the high-speed mixer, and stirred at 700 rpm for 5 minutes at room temperature to obtain a premix, in which PVC The mass ratio of resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant is 2:1:0.3:0.3:0.2:0.1:0.3:0.2, and then the mixed premix is added to the twin-screw extruder, and the strips are extruded through the extruder, and then the extruded strips are cooled and cut into PVC particles, wherein the temperature of the extruder is 170°C, and then the PVC particles are quickly cooled through a cooling water bath, and then dried at room temperature to remove moisture on the surface of the particles, and then The PVC particles are crushed by a high-speed rotating grinder, and then screened by a filter to obtain a modified environmentally friendly flame-retardant PVC powder, and then fumed silica is added to the modified environmentally friendly flame-retardant PVC powder, and stirred evenly to obtain a mixed powder, and then the mixed powder is placed in a fluidized bed, and nitrogen is supplied to the fluidized bed at an air flow rate of 50 cm / s to make the modified environmentally friendly flame-retardant PVC powder form a suspended state in the fluidized bed, and the modified environmentally friendly flame-retardant PVC powder in a fluidized state is obtained for standby use, wherein the temperature of the fluidized bed is maintained at 70°C.
[0023] Furthermore, the tensile strength was 49 MPa, the elongation at break was 320%, the tensile strength after heat aging treatment at 100°C for 168 h was 37 MPa, the elongation at break was 260%, the corrosion resistance was good, and the flame retardant grade was V-1.
[0024] Embodiment 2: Step S3: preparing modified environmentally friendly flame-retardant PVC powder: firstly, mixing basic magnesium sulfate whiskers with deionized water, stirring at 40 rpm for 20 min, and heating to 70°C, then adding a surface modifier thereto and continuing stirring for 15 min to obtain a modified basic magnesium sulfate whisker solution, wherein the mass ratio of basic magnesium sulfate whiskers to surface modifier is 10:1 solution, cooling the solution to room temperature and then washing with clean water, and then drying at room temperature to obtain modified basic magnesium sulfate whiskers, and then drying the obtained modified basic magnesium sulfate whiskers The mixture was mixed with bisphenol A-bis(diphenyl phosphate) at a mass ratio of 1:1 at 50°C to obtain a halogen-free compound flame retardant. Then, PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant and antioxidant were placed in a high-speed mixer and stirred at 700 rpm for 15 minutes at 85°C, then cooled to room temperature, and then the halogen-free compound flame retardant and smoke suppressant were added to the high-speed mixer, and stirred at 700 rpm for 5 minutes at room temperature to obtain a premix, in which PVC The mass ratio of resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant is 2:1:0.6:0.3:0.2:0.1:0.3:0.2, and then the mixed premix is added to the twin-screw extruder, and the strips are extruded through the extruder, and then the extruded strips are cooled and cut into PVC particles, wherein the temperature of the extruder is 170°C, and then the PVC particles are quickly cooled through a cooling water bath, and then dried at room temperature to remove moisture on the surface of the particles, and then The PVC particles are crushed by a high-speed rotating grinder, and then screened by a filter to obtain a modified environmentally friendly flame-retardant PVC powder, and then fumed silica is added to the modified environmentally friendly flame-retardant PVC powder, and stirred evenly to obtain a mixed powder, and then the mixed powder is placed in a fluidized bed, and nitrogen is supplied to the fluidized bed at an air flow rate of 50 cm / s to make the modified environmentally friendly flame-retardant PVC powder form a suspended state in the fluidized bed, and the modified environmentally friendly flame-retardant PVC powder in a fluidized state is obtained for standby use, wherein the temperature of the fluidized bed is maintained at 70°C.
[0025] Furthermore, the tensile strength was 53 MPa, the elongation at break was 360%, the tensile strength after heat aging treatment at 100°C for 168 h was 41 MPa, the elongation at break was 290%, the corrosion resistance was good, and the flame retardant grade was V-0.
[0026] Embodiment three: Step S3: preparing modified environmentally friendly flame-retardant PVC powder: firstly, mixing basic magnesium sulfate whiskers with deionized water, stirring at 40 rpm for 20 min, and heating to 70°C, then adding a surface modifier thereto and continuing stirring for 15 min to obtain a modified basic magnesium sulfate whisker solution, wherein the mass ratio of basic magnesium sulfate whiskers to surface modifier is 10:1 solution, cooling the solution to room temperature and then washing with clean water, and then drying at room temperature to obtain modified basic magnesium sulfate whiskers, and then drying the obtained modified basic magnesium sulfate whiskers The mixture was mixed with bisphenol A-bis(diphenyl phosphate) at a mass ratio of 2:3 at 50°C to obtain a halogen-free composite flame retardant. Then, PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant and antioxidant were placed in a high-speed mixer and stirred at 700 rpm for 15 min at 85°C, then cooled to room temperature, and then the halogen-free composite flame retardant and smoke suppressant were added to the high-speed mixer, and stirred at 700 rpm for 5 min at room temperature to obtain a premix, in which PVC The mass ratio of resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant is 2:1:0.9:0.3:0.2:0.1:0.3:0.2, and then the mixed premix is added to the twin-screw extruder, and the strips are extruded through the extruder, and then the extruded strips are cooled and cut into PVC particles, wherein the temperature of the extruder is 170°C, and then the PVC particles are quickly cooled through a cooling water bath, and then dried at room temperature to remove moisture on the surface of the particles, and then The PVC particles are crushed by a high-speed rotating grinder, and then screened by a filter to obtain a modified environmentally friendly flame-retardant PVC powder, and then fumed silica is added to the modified environmentally friendly flame-retardant PVC powder, and stirred evenly to obtain a mixed powder, and then the mixed powder is placed in a fluidized bed, and nitrogen is supplied to the fluidized bed at an air flow rate of 50 cm / s to make the modified environmentally friendly flame-retardant PVC powder form a suspended state in the fluidized bed, and the modified environmentally friendly flame-retardant PVC powder in a fluidized state is obtained for standby use, wherein the temperature of the fluidized bed is maintained at 70°C.
[0027] Furthermore, the tensile strength was 52 MPa, the elongation at break was 360%, the tensile strength after heat aging treatment at 100°C for 168 h was 39 MPa, the elongation at break was 292%, the corrosion resistance was good, and the flame retardant grade was V-0.
[0028] Comparative Example: The existing all-plastic compensation chain is used as a comparative example, wherein the tensile strength is 34MPa, the elongation at break is 240%, the tensile strength after heat aging treatment at 100℃ for 168h is 21MPa, the elongation at break is 160%, the corrosion resistance is general, and the flame retardant grade is V-2.
[0029] The results of the mechanical property test, corrosion resistance test and flame retardant property test of the plastic dip flame retardant elevator balance compensation chain are as follows:
[0030] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A plastic dip flame retardant elevator balance compensation chain, characterized by: Including the following raw materials: modified high-strength alloy and modified environmentally friendly flame-retardant PVC powder; The modified high-strength alloy is prepared by subjecting the high-strength alloy to plasma surface modification treatment; The modified environmentally friendly flame-retardant PVC powder is prepared from PVC resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant in a mass ratio of 2:1:(0.1-1):0.3:0.2:0.1:0.3:0.2; The modified high-strength alloy is assembled into a compensation chain, and then the preheated compensation chain is completely immersed in modified environmentally friendly flame-retardant PVC powder to obtain a flame-retardant compensation chain, which has better flame-retardant properties than the existing plastic-coated compensation chain.
2. According to claim 1, a plastic-impregnated flame-retardant elevator balance compensation chain is characterized in that: The halogen-free composite flame retardant is prepared by mixing modified basic magnesium sulfate whiskers and bisphenol A-bis(diphenyl phosphate) in a mass ratio of 2:(1-4).
3. The plastic-impregnated flame-retardant elevator balance compensation chain according to claim 1, characterized in that: The particle size of the modified environmentally friendly flame-retardant PVC powder is 1-3 mm.
4. A method for preparing a plastic dip flame retardant elevator balance compensation chain, applicable to a plastic dip flame retardant elevator balance compensation chain according to any one of claims 1 to 3, characterized in that: The preparation method of the plastic-impregnated flame-retardant elevator balance compensation chain is as follows: Step S1: material pretreatment: performing plasma surface modification treatment on the high-strength alloy to obtain a modified high-strength alloy, and selecting the modified high-strength alloy of qualified quality as the preparation raw material; Step S2: Chain production and assembly: Cut and shape the qualified modified high-strength alloy selected in step S1 to make standard chain links, and then connect and weld the chain links one by one to form a complete compensation chain; Step S3: preparing modified environmentally friendly flame-retardant PVC powder: mixing PVC resin, ABS resin, halogen-free compound flame retardant, heat stabilizer, plasticizer, lubricating dispersant, antioxidant and smoke suppressant in a mass ratio of 2:1:(0.1-1):0.3:0.2:0.1:0.3:0.2 to prepare environmentally friendly flame-retardant PVC, then grinding the environmentally friendly flame-retardant PVC into powder, and fluidizing the powder for standby use; Step S4: plastic dipping: the compensation chain obtained in step S2 is subjected to plastic dipping treatment to form a protective layer on the surface of the compensation chain; Step S5: Performance test: The compensating chain obtained in step S4 is subjected to mechanical property test, corrosion resistance test and flame retardant property test.
5. The method for preparing a plastic-impregnated flame-retardant elevator balance compensation chain according to claim 4, characterized in that: The step S1 further includes the following steps: Step S11: Materials and cleaning: First, clean the high-strength alloy with clean water to remove dust and oil on the surface; Step S12: Surface cleaning: The high-strength alloy cleaned in step S11 is then placed in a low-temperature vacuum plasma surface treatment apparatus, and the oxides and other stubborn contaminants on the surface of the high-strength alloy are removed by plasma cleaning technology in a vacuum environment; Step S13: Surface etching: Physically etching the high-strength alloy cleaned in step S12 to make the surface of the high-strength alloy rough; Step S14: Surface activation: Then, the high-strength alloy etched in step S13 is plasma activated to change the chemical activity of the surface of the high-strength alloy; Step S15: plasma polymerization: methane gas is then introduced into the low-temperature vacuum plasma surface treatment apparatus to perform a polymerization reaction in a plasma state to form a 1-2 mm polymer coating on the surface of the high-strength alloy; Step S16: Subsequent treatment: Finally, heat treatment is performed on the high-strength alloy polymerized in step S15; Step S17: Quality screening: Perform adhesion test and corrosion resistance test on the modified high-strength alloy according to the provisions of GB / T38020.2-2019, and remove unqualified modified high-strength alloy.
6. The method for preparing a plastic-impregnated flame-retardant elevator balance compensation chain according to claim 4, characterized in that: The step S2 further includes the following steps: Step S21: cutting: using a laser cutting machine to cut the modified high-strength alloy; Step S22: Cleaning: Then use an ultrasonic cleaning machine to clean the cut alloy to remove debris and impurities on the surface; Step S23: forming: using a chain forming machine to bend and press the alloy cleaned in step S22 to form chain links; Step S24: Assembling: connecting the formed chain links one by one to form a continuous chain by an automated welding robot; Step S25: Screening: Use visual inspection equipment to detect whether the size of the chain formed in step S24 meets the predetermined size standard, and screen out chains with unqualified sizes.
7. The method for preparing a plastic-impregnated flame-retardant elevator balance compensation chain according to claim 4, characterized in that: The step S3 further includes the following steps: Step S31: mixing the basic magnesium sulfate whisker with deionized water, stirring at a speed of 30-50 rpm for 10-20 minutes, and heating to 70°C, then adding a surface modifier thereto and continuing stirring for 15 minutes to obtain a modified basic magnesium sulfate whisker solution, wherein the mass ratio of the basic magnesium sulfate whisker to the surface modifier is 10:1, cooling the solution to room temperature, washing with clean water, and then drying at room temperature to obtain modified basic magnesium sulfate whiskers; Step S32: mixing the modified basic magnesium sulfate whisker obtained in step S31 with bisphenol A-bis(diphenyl phosphate) in a mass ratio of 2:(1-4) at 40-50° C. to obtain a halogen-free composite flame retardant; Step S33: placing PVC resin, ABS resin, heat stabilizer, plasticizer, lubricating dispersant and antioxidant in a high-speed mixer, stirring at 650-800 rpm for 15 min at 85-90° C., then cooling to room temperature, then adding halogen-free composite flame retardant and smoke suppressant to the high-speed mixer, and continuing to stir at 650-800 rpm for 5 min at room temperature to obtain a premix; Step S34: adding the premixed material in step S33 into a twin-screw extruder, extruding strips through the extruder, and then cooling the extruded strips and cutting them into PVC particles, wherein the temperature of the extruder is 165-170° C.; Step S35: Rapidly cool the PVC particles in step S34 by passing through a cooling water bath, and then dry them at room temperature to remove moisture from the surface of the particles; Step S36: The PVC particles are then crushed by a high-speed rotating grinder, and then screened by a filter to obtain modified environmentally friendly flame-retardant PVC powder; Step S37: Then add the fumed silica to the modified environmentally friendly flame-retardant PVC powder, stir evenly to obtain a mixed powder, and then place the mixed powder in a fluidized bed, supply nitrogen to the fluidized bed at an air flow rate of 40 to 60 cm / s, so that the modified environmentally friendly flame-retardant PVC powder forms a suspended state in the fluidized bed, and obtain the modified environmentally friendly flame-retardant PVC powder in a fluidized state for use.
8. The method for preparing a plastic-impregnated flame-retardant elevator balance compensation chain according to claim 4, characterized in that: The step S4 further includes the following steps: Step S41: firstly install the compensation chain on the hanger, and then preheat the compensation chain on the hanger, wherein the heating temperature of the preheating treatment is 180° C. to 200° C., and the heating time is 10 minutes; Step S42: then immerse the preheated compensation chain in a fluidized bed filled with modified environmentally friendly flame-retardant PVC powder in a fluidized state for 5-10 minutes, and then send the dipped compensation chain into an oven for heating and curing at a temperature of 190°C to 200°C for 2 minutes; Step S43: Then, the baked compensation chain is subjected to air cooling treatment to fix the coating on the surface of the compensation chain, and then the cooled compensation chain is removed from the hanger.
9. The method for preparing a plastic-impregnated flame-retardant elevator balance compensation chain according to claim 4, characterized in that: The step S5 further includes the following steps: Step S51: inspect the mechanical properties of the compensation chain according to the inspection method specified in GB / T2951.11-2008, and then conduct a neutral salt spray test for 360 hours according to the method specified in GB / T10125-2012. Then, determine whether the measured breaking load is lower than the minimum breaking load of the compensation chain according to the method specified in T / CEA0027-2021, so as to determine the corrosion resistance of the compensation chain; Step S52: Flame retardant performance test: fix the compensation chain sample vertically on the sample fixture in the combustion tube, use the igniter to ignite the top of the sample, introduce a mixed gas of oxygen and nitrogen into it, and adjust the flow ratio of oxygen and nitrogen to measure the minimum oxygen concentration that can just maintain combustion to evaluate the flame retardant performance of the compensation chain.
10. The method for preparing a plastic-impregnated flame-retardant elevator balance compensation chain according to claim 7, characterized in that: In step S37, the temperature of the fluidized bed is maintained at 60°C-70°C.
Citation Information
Patent Citations
Preparation method of environment-friendly high-speed elevator compensation chain sheathing material
CN103865200B
A halogen-free, environmentally friendly high-speed elevator compensation chain material and its application
CN104140600B
Manufacturing process of aging-resistant elevator compensation cable
CN106245390B